Influence of experimental conditions on localized surface plasmon resonances measurement by electron energy loss spectroscopy - Horák, Michal; Šikola, Tomáš (Ultramicroscopy, 2020)
Scanning transmission electron microscopy (STEM) combined with electron energy loss spectroscopy (EELS) has become a standard technique to map localized surface plasmon resonances with a nanometer spatial and a sufficient energy resolution over the last 15 years. However, no experimental work discussing the influence of experimental conditions during the measurement has been published up to now. We present an experimental study of the influence of the primary beam energy and the collection semi-angle on the plasmon resonances measurement by STEM-EELS. To explore the influence of these two experimental parameters we study a series of gold rods and gold bow-tie and diabolo antennas. We discuss the impact on experimental characteristics which are important for successful detection of the plasmon peak in EELS, namely: the intensity of plasmonic signal, the signal to background ratio, and the signal to zero-loss peak ratio. We found that the primary beam energy should be high enough to suppress the scattering in the sample and at the same time should be low enough to avoid the appearance of relativistic effects. Consequently, the best results are obtained using a medium primary beam energy, in our case 120 keV, and an arbitrary collection semi-angle, as it is not a critical parameter at this primary beam energy. Our instructive overview will help microscopists in the field of plasmonics to arrange their experiments.
Keywords: EELS; Primary beam energy; Collection semi-angle; Localized surface plasmon resonance; Electron energy loss spectroscopy